2020
DOI: 10.1051/e3sconf/202016800042
|View full text |Cite
|
Sign up to set email alerts
|

Present problems of vibration isolation in heavy mining machines at long-term cyclic loads

Abstract: On the basis of the developed simulation model and the Boltzmann-Volterra integral relations with kernels of relaxation and aftereffect, an equation was worked out, which made it possible to take into account the rubber viscoelastic properties in full volume; in this equation, stiffness operator of elastic suspension in the machine is written by using fractional exponential function of the Yu. Rabotnov’s type; on the basis of the mathematical model, the basic parameters of the machine under the study were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It is necessary to continue the installation of engineering and seismometric service stations on high-rise buildings, on buildings with new constructive solutions, including objects with various seismic isolation systems [10][11][12][13][14][15] and buildings with pile foundations [17].…”
Section: The Discussion Of the Resultsmentioning
confidence: 99%
“…It is necessary to continue the installation of engineering and seismometric service stations on high-rise buildings, on buildings with new constructive solutions, including objects with various seismic isolation systems [10][11][12][13][14][15] and buildings with pile foundations [17].…”
Section: The Discussion Of the Resultsmentioning
confidence: 99%
“…Once again, it has been confirmed that earthquake sources can be located both on the territory of the city of Almaty and outside it. Therefore, the use of seismic-insulating foundations of various types remains relevant, which will reduce seismic loads by moving the building as a solid body without deformation of the above-foundation part [10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%